1995
DOI: 10.1073/pnas.92.10.4158
|View full text |Cite
|
Sign up to set email alerts
|

Function of the oxidative burst in hypersensitive disease resistance.

Abstract: Consistent with the mechanism for phagocyte oxidase activation, elicitor induction of H202 production in soybean cells is blocked by the protein kinase inhibitors K252A and staurosporine, and this inhibition is partially reversed by simulta-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
216
0
5

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(224 citation statements)
references
References 29 publications
3
216
0
5
Order By: Relevance
“…Furthermore, AOS generation could also be stimulated by the phorbol ester PMA, a potent activator of protein kinase C and the respiratory burst in neutrophils [8]. To our knowledge, PMA has so far only been observed to promote AO$ generation in soybean (A. Levine, unpublished data, from [17]). Since it is known that PMA stimulates NADPH oxidas¢ activity in neutrophils via phosphorylation of its cytosolic component [8,9] it is possible that a protein kinase C-like enzyme might bo involved in AO$ generation in Arabido~i~.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, AOS generation could also be stimulated by the phorbol ester PMA, a potent activator of protein kinase C and the respiratory burst in neutrophils [8]. To our knowledge, PMA has so far only been observed to promote AO$ generation in soybean (A. Levine, unpublished data, from [17]). Since it is known that PMA stimulates NADPH oxidas¢ activity in neutrophils via phosphorylation of its cytosolic component [8,9] it is possible that a protein kinase C-like enzyme might bo involved in AO$ generation in Arabido~i~.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence that the primary AOS is superoxide has been presented for cultured spruce [14] and tomato [15] cells and inhibitor studies with elicited rose cells have demonstrated striking parallels with the mammalian NADPH oxidase [16]. Furthermore, soybean proteins immunologically related to components of the mammalian complex have been reported recently [17].…”
Section: Introductionmentioning
confidence: 99%
“…In plants, it occurs in response to abiotic and biotic factors and plays an essential role in plant development and survival (Greenberg, 1996). Cell death was described in reproductive processes as well as during vegetative growth (Greenberg, 1996;Beers, 1997), during stress adaptation, such as during low oxygen stress (Kawai et al, 1998;Samarajeewa et al, 1999), and as a defense mechanism against pathogens (Tenhaken et al, 1995;Ryerson and Heath, 1996;Chappell et al, 1997;Gechev et al, 2004).…”
mentioning
confidence: 99%
“…Recently, it has been recognized that a number of "stress" genes of previously unidentified functions make u p a plant GST subclass (for reviews, see Droog et al, 1993;Marrs, 1996). These type I11 GSTs are induced by numerous environmental stress conditions, including those arising from pathogen attack (Taylor et al, 1990), oxidative stress (Wingate et al, 1988;Levine et al, 1994;Tenhaken et al, 1995), and heavy metal toxicity (Czarnecka et al, 1988;Hagen et al, 1988;Wingate et al, 1988;Mauch and Dudler, 1993). The type I11 GSTs also play a role in the cellular response to both natural and synthetic auxins (Droog et al, 1993;Hahn and Strittmatter, 1994;Ulmasov et al, 1994Ulmasov et al, , 1995Droog, 1995;Droog et al, 1995).…”
mentioning
confidence: 99%